2008
DOI: 10.1002/pen.21013
|View full text |Cite
|
Sign up to set email alerts
|

The mastication characteristics of powdered carbon black filled natural rubber during internal mixing

Abstract: Powdered carbon black filled natural rubber, P(NR/ HAF), is a premixture of natural rubber and carbon black in powdered form with good carbon black dispersion throughout the rubber matrix. In this study, the mastication properties of P(NR/HAF) were observed under a wide temperature range (50-1108C) and rotor speed (30-100 rpm) range, using a mixing head attached to Brabender Plasticorder. It was found that P(NR/HAF) showed different mastication characteristic, compared to the traditional internal mastication t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The molecular weight of gum natural rubber is very high which leads to strong elastic properties and difficulty in processing. Mastication is one of the basic steps for natural rubber processing which during mastication step, long chains of gum natural rubber are cut into shorter chains to rapidly decrease the viscosity of the rubber [17]. Figure 1 showed that shear force due to mastication process reduced the molecular weight of SMR CV60 faster than SVR 3L.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular weight of gum natural rubber is very high which leads to strong elastic properties and difficulty in processing. Mastication is one of the basic steps for natural rubber processing which during mastication step, long chains of gum natural rubber are cut into shorter chains to rapidly decrease the viscosity of the rubber [17]. Figure 1 showed that shear force due to mastication process reduced the molecular weight of SMR CV60 faster than SVR 3L.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11] The traditional dry mixing (DM) process is difficult to disperse silica evenly in the rubber matrix. 12 Wet mixing is an effective method to improve the interfacial compatibility between silica and rubber and to make silica more evenly dispersed in the rubber. [13][14][15][16][17][18][19] Acid coagulation is the most traditional coagulation process in the wet mixing of rubber latex.…”
Section: Introductionmentioning
confidence: 99%
“…However, the surface of silica is rich in silicon hydroxyl groups, which are easily adsorbed to each other to produce larger aggregates, and the interfacial compatibility with non‐polar rubber is poor 9–11 . The traditional dry mixing (DM) process is difficult to disperse silica evenly in the rubber matrix 12 . Wet mixing is an effective method to improve the interfacial compatibility between silica and rubber and to make silica more evenly dispersed in the rubber 13–19 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the dispersity of the fillers in rubber is poor, and the energy consumption and dust pollution exist. [ 14,15 ] Compared with traditional dry mixing technology, the wet‐mixing technology significantly improves the dispersion of reinforcing fillers in rubber, reduces energy consumption, and production costs. [ 16,17,18 ] Wang et al [ 19,20 ] prepared highly dispersed silica/NR composites by atomization combined with high‐temperature sputtering method.…”
Section: Introductionmentioning
confidence: 99%